2016
DOI: 10.5812/aapm.30071
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Etomidate Versus Combination of Propofol-Ketamine and Thiopental-Ketamine on Hemodynamic Response to Laryngoscopy and Intubation: A Randomized Double Blind Clinical Trial

Abstract: Background:Laryngoscopy and intubation frequently used for airway management during general anesthesia, is frequently associated with undesirable hemodynamic disturbances.Objectives:The aim of this study was to compare the effects of etomidate, combination of propofol-ketamine and thiopental-ketamine as induction agents on hemodynamic response to laryngoscopy and intubation.Patients and Methods:In a double blind, randomized clinical trial a total of 120 adult patients of both sexes, aged 18 - 45 years, schedul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 24 publications
1
10
1
Order By: Relevance
“…Propofol is one of the most commonly used intravenous anesthetic agents and is widely used in various kinds of cancer resections due to its rapid onset and short duration of action 5 . Numerous studies have recently found that propofol is able to influence the cell proliferation, migration, and invasiveness of cancers, such as ovarian cancer 6 , breast cancer 7 , liver cancer 8 , and lung cancer 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Propofol is one of the most commonly used intravenous anesthetic agents and is widely used in various kinds of cancer resections due to its rapid onset and short duration of action 5 . Numerous studies have recently found that propofol is able to influence the cell proliferation, migration, and invasiveness of cancers, such as ovarian cancer 6 , breast cancer 7 , liver cancer 8 , and lung cancer 9 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 33 ] Combination of ketamine and propofol (ketofol) is a popular combination with few studies reporting its efficacy. [ 34 35 ] Our survey found the use of propofol and ketamine in 44% of the respondents. Choice of induction agent is not uniform among respondents that are quite understandable due to heterogeneity in the patient population.…”
Section: Discussionmentioning
confidence: 97%
“…In spite of the potential benefits of using etomidate as an induction agent, one area of concern exists regarding its use in anesthesia. Researchers believe that etomidate could possibly lead to profound and persistent adrenocortical steroid synthesis [ 40 ]. However, the evidence surrounding this concern is conflicting, and the effect of a single bolus of etomidate on patient morbidity and mortality remains unclear [ 41 ].…”
Section: Discussionmentioning
confidence: 99%